The central role of gastrin in gastric cancer - Waldum, Helge; Mjønes, Patricia (Frontiers in Oncology, 2023)
The prevalence of gastric cancer has markedly declined, but due to high mortality it is still an important 9 disease The preferred classification of gastric cancer is according to Lauren into intestinal type with a glandular 10 growth pattern and diffuse type without glandular structures. Both types were classified as adenocarcinomas, the 11 latter type based on periodic acid-Schiff (PAS) positivity presumed to reflect mucin. However, the presence of mucin 12 in the diffuse type has not been confirmed by immunohistochemistry and in-situ hybridization in contrast to 13 neuroendocrine/enterochromaffin-like (ECL) cell markers. The ECL cell is probably prone to become cancer since it 14 does not express E-cadherin. Gastric cancer is unique in that a bacterium, H. pylori, is thought to be the main cause. 15 H. pylori predisposes to cancer only after having caused oxyntic atrophy leading to gastric hypoacidity and 16 hypergastrinemia. No single H. pylori factor has convincingly proved to be carcinogenic. It is probable that gastrin is 17 the pathogenetic factor for gastric cancer due to H. pylori , autoimmune gastritis, and long-term prolonged inhibition 18 of gastric acid secretion. Hypergastrinemia induces ECL cell hyperplasia which develops into neuroendocrine 19 tumours (NETs) and further to neuroendocrine carcinomas in rodents, a sequence also described in man. During 20 carcinogenesis the tumour cells lose specific traits requiring sensitive methods to recognize their origin. Gastric 21 cancer occurrence may hopefully be prevented by H. pylori eradication at young age, reduction of use of inhibitors 22 of acid secretion and use of a gastrin antagonist in those with previous long-term H. pylori infection as well as those 23 with autoimmune gastritis.